PENERAPAN MODEL BELAJAR KONSTRUKTIVISME UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI MEMPERBAIKI SISTEM PENGAMAN KELISTRIKAN DAN KOMPONENNYA DI SMKN 1 TANGGEUNG KABUPATEN CIANJUR - Aditya Mahatma Yodha, - (2011)
This study was conducted based on several research problems; (1) learning process at school on repairing electrical safety system subject which is more practical tends to be focused on accomplishment of curricula, it is more important to memorize the concepts than to understand them; (2) teacher is more interested in lecturing students to present the subject materials, that is not varied, not interesting for students, ignoring their curiosity, making them bored, in which the students only have to sit, pay attention to the lectures and take some notes for them, and there is no opportunity for the students to question their tacit assumptions on the subject materials. Learning activity should provide learning situation in which the students are actively involved in it, such as asking their questions, responding to the question whether it comes from other students or the teacher, asking for and giving estimation, or even doing some demonstrations for the subject; (3) students' learning achievement on repairing electrical safety system subject at SMKN 1 Tanggeung showed there was 60% of students were still at low level. The objective of the study is to improve students' learning achievement on subject of repairing electrical safety system and its components in a vocational public school, SMKN 1 Tanggeung at district of Cianjur, particularly Grade XI of Teknik Mekanik Otomotif class, using constructivism learning model. This study applied classroom action research as the research method within three cycles of observation. The findings revealed some escalations in students' learning achievement for each of cycles. The achievement at cycle I shows that 84,70% of students passed at A-level, at cycle II shows 88,72% of students passed at A-level, and at cycle III shows 91,99% of students passed at A-plus-level. The learning activity for each cycle has improvement, the average point of the result on students' learning achievement for each cycle, that is; cycle I has 62,59% (high), cycle II 75,18% (high), and cycle III 89,62% (very high). According to the data analysis, it is summarized that applying constructivism learning model improve students' learning activity and their learning achievement on subject of repairing electrical safety system and its components in SMKN 1 Tanggeung at district of Cianjur. Penelitian ini dilatar belakangi oleh beberapa permasalahan diantaranya: (1) proses pembelajaran yang berlangsung di sekolah pada mata pelajaran produktif yang lebih bersifat praktis masih cenderung ditujukan pada pencapaian target kurikulum, lebih mementingkan penghafalan konsep bukan pemahaman; (2) Guru seringkali menggunakan metode ceramah dalam penyampaian materi, yang cenderung monoton, mengabaikan minat anak, kurang menarik, kurang menyenangkan, dan segera membosankan, dimana siswa hanya duduk, mencatat dan mendengarkan apa yang disampaikannya dan sedikit peluang bagi siswa untuk bertanya. Seharusnya, kegiatan belajar itu membuat siswa aktif seperti bertanya, menjawab, mengeluarkan pendapat bahkan melakukan peragaan atau melakukan suatu aktivitas; (3) Hasil belajar siswa pada materi memperbaiki sistem pengaman kelistrikan dan komponennya di SMKN 1 Tanggeung Kabupaten Cianjur masih kurang maksimal terdapat 60% yang tidak lulus. Tujuan penelitian ini adalah untuk meningkatkan hasil belajar siswa pada materi memperbaiki sistem pengaman kelistrikan dan komponennya dengan menggunakan model belajar konstruktivisme pada siswa kelas XI Teknik Mekanik Otomotif SMKN 1 Tanggeung Kabupaten Cianjur. Metode penelitian yang digunakan ialah Penelitian Tindakan Kelas (PTK) yang dilaksanakan dalam tiga siklus. Hasil penelitian yang diperoleh menunjukkan peningkatan hasil belajar siswa pada setiap siklusnya. Hasil belajar pada siklus I sebesar 84,70 (lulus dengan predikat baik), pada siklus II sebesar 88,72 (lulus dengan predikat baik), dan pada siklus III sebesar 91,99 (lulus dengan predikat amat baik). Aktivitas belajar siswa pada setiap siklus pembelajaran juga mengalami peningkatan, hasil rata-rata aktivitas siswa untuk setiap siklusnya yaitu; siklus I 62,59% (tinggi), meningkat pada siklus II menjadi 75,18% (tinggi), Siklus III menjadi 89,62% (sangat tinggi). Berdasarkan analisis data hasil penelitian yang diperoleh di lapangan maka dapat disimpulkan bahwa penerapan model belajar konstruktivisme dapat meningkatkan hasil belajar dan aktivitas belajar siswa pada materi memperbaiki sistem pengaman kelistrikan dan komponennya di SMKN 1 Tanggeung Kabupaten Cianjur.